Safety & Security Analysis of Sea Transportation in Indonesia - Faturachman, Danny; Shariman, Mustafa (2013)
Indonesia waters as a liaison between the city and the island, also has a variety of wealth which became the object of the future welfare of the people hope. For these necessary safeguards particularly against sea cruise in the area of maritime safety because Indonesia greatly affect development efforts, especially the continuation of transport activity. Maritime transport holds a very important role in maritime countries, such as in Indonesia whose territory is an archipelago. Associated with maritime transport, there are three aspects that are interlinked with each other, i.e. traffic and sea transportation, port and also the safety and security of the cruise.